Yield of lady finger banana alley cropped in a system with Inga spp., at varying levels of potassium and phosphorus fertilizers - Reyes Osornio, Maribel; Guzman-Moreno, M. A.; Catari-Yujra, G.; Hernández Hernández, Hipólito; Gutiérrez Hernández, José Orbelin (Universidad Autónoma de Yucatán, 2023)
Background: the agronomic yield of crops of importance for rural households in the humid tropics, such as banana, cultivated in association with leguminous trees, such as Inga spp., must be studied because of the little available information on that association, especially with regards to yield response to the application of P and K under agroforestry systems, and the interaction between organic (leguminous residues) and inorganic sources of nutrients. Objective: the objective of this study was to evaluate the yield of lady finger banana alley cropped with Inga spp., under several levels of natural fertilizers such as K2SO4 + Mg, and phosphoric rock (RF). Methodology: Yield response of lady finger banana (Musa acuminata Colla) under an alley cropping system with guama (Inga spp.). Prior to the establishment of the crop, dolomitic lime (Ca3(PO4)2CaF2) at a rate of 2 ton ha-1 was applied. In addition, phosphoric rock (RF) was added to the crop at diverse levels (0, 20, 40, 80 kg ha-1), and potassium sulphate and magnesium (K2SO4 + Mg) at three levels (0, 45, 90 kg ha-1) with five replicates in a total of 35 alleys for treatments. Inga spp. trees provided with nitrogen (N). Two crop cycles were evaluated, cycle 1 (2015) and cycle 2 (2017). Results: the highest average weight per bunch were obtained with 80 FP and 0 RF in the first cycle, and with 90 K and 45 K in the second cycle, which were significantly higher than other levels. The highest yield on yearly basis was 45 K among the treatments during the first cycle, and the highest yields during the second cycle were obtained with 45 y 90 K2SO4 + Mg. Implications: There are no prior studies for lady finger banana crop associated with Inga spp. trees under alley cropping, this reflects that the study is an original contribution to nutrient-response studies under agroforestry system with Inga. Conclusion: the highest yields were obtained with 90 and 45 kg ha-1 of potassium sulphate and magnesium. The application of dolomitic lime promoted P and K availability for the crop, and better use of applied K2SO4 + Mg and of RF in the treatments.
Keywords: Musa acuminada; Guama; Roca fosfórica; Sulfato de potasio y magnesio